AERODYNAMICS OF A SPHERICAL BASED SPOUTED BED - Evin, Duygu; Tanyildizi, Vedat (Yildiz Technical Univ, 2007)
The experimental findings belong to the conventional cone based spouted beds show that, the individual particles in the annular part of the bed move vertically downward and radially inward, describing approximately parabolic trajectories. In this study, the shape of the jacket is arranged by conforming to parabolic trajectories of the particles as much as possible for eliminating or decreasing the dead zone. To ensure this, a cylindrical spouted bed with spherical base is used as closest shaped one and hydrodynamics of this spouted bed is investigated experimentally. This study includes experimental results of spherical based spouted bed of different materials for various operating parameters (H, U). Effects of bed height (H) and properties of the solid particles on minimum spouting velocity, peak pressure drop and steady spouting pressure drop (onset of spouting) are determined.
Keywords: Spouted bed; spherical base; pressure drop